Is There A Link Between Climate Change and Human Health? - Sutrisno, MD, PhD OG (REI) (Asian Journal of Health Research, 2022)
According to the final report of the Lancet panel on climate change [1,2], " climate change is the biggest global danger of the 21st century". The world's climate has permanently changed over time. Some regions of the Earth that are presently relatively warm were once covered in ice millions of years ago. In more recent decades, average temperatures have cycled up and down due to variations in solar radiation or the recurrent eruption of volcanoes [3]. There is broad scientific agreement that Human-caused greenhouse gas emissions are a vital contributor to global warming that is currently taking place. Global carbon dioxide emissions are rising, reaching a new high last year. Indonesians seek to fight the risk of poverty being undermined by climate change. Its effects are escalating the dangers and vulnerabilities that face the poor, adding to the strain on their already overworked coping mechanisms. Infectious diseases, malnutrition, stunting, degenerative diseases, cancer, autoimmune disease, maternal and perinatal mortality, and many more having close connection with climate change. Natural disaster to be more prevalent and aggravates the bad impact.  It is need to addresses the effects of climate change on health, contemporary sociopolitical views, and the need for public health and climate change policy that places a strong emphasis on the advantages to manage climate changes in reducing health impact in Indonesia and around the world [4].